Inside/Outside: Post‐Synthetic Modification of the Zr‐Benzophenonedicarboxylate Metal–Organic Framework. Issue 10 (4th February 2020) - Mohmeyer, Alexander; Schäfer, Malte; Schaate, Andreas; Locmelis, Sonja; Schneider, Andreas M.; Behrens, Peter
Abstract: The Zr‐based metal–organic framework, Zr‐ bzpdc ‐MOF, contains the photoreactive linker molecule benzophenone‐4, 4′‐dicarboxylate ( bzpdc ) which imparts the possibility for photochemical post‐synthetic modification. Upon irradiation with UV light, the keto group of the benzophenone moiety will react with nearly every C−H bond‐containing molecule. Within this paper, we further explore the photochemical reactivity of the Zr‐ bzpdc ‐MOF, especially with regard to which restrictions govern internal versus external reactions. We show that apart from reactions with C−H bond‐containing molecules, the MOF reacts also with water. By studying the reactivity versus linear alcohols we find a clear delineation in that shorter alcohol molecules (up to butanol as a borderline case) react with photoexcited keto groups throughout the whole crystals whereas longer ones react only with surface‐standing keto groups. In addition, we show that with the alkanes n ‐butane to n ‐octane, the reaction is restricted to the outer surface. We hypothesize that the reactivity of the Zr‐ bzpdc ‐MOF versus different reagents depends on the accessibility of the pore system which in turn depends mainly on the size of the reagents and on their polarity. The possibility to direct the post‐synthetic modification of the Zr‐ bzpdc ‐MOF (selective modification of the whole pore system versus surface modification) gives additional degrees of freedom in the design of this metal–organic framework for shaping and for applications. Abstract : Inside/Outside : The photochemical post‐synthetic modification of the Zr‐benzophenone‐dicarboxylate‐MOF can be directed to occur only on the surface or throughout the whole crystals, providing additional possibilities to selectively introduce novel functionalities and tailor the properties of this MOF. Major control parameters are size and polarity of the modifying reagent.